PWE-162 Concurrent Computerised Tomography Can Optimise the Detection of Cancer in Patients Presenting with Unexplained Anaemia. (4th June 2013) - Bains, J; Mansukhani, S; Coates, S; Pinato, D J; Mendall, M A
Abstract : Introduction: Active investigation for gastrointestinal (GI) cancers is often triggered by "alarm symptoms"; features in the clinical presentation that may predict malignancy and warrant urgent referral. Unexplained anaemia (UA) is a highly prevalent presentation. The BSG guidelines recommend only upper GI endoscopy (OGD) and colonoscopy (COL). We investigated the additional diagnostic value of concurrent contrast enhanced computerised tomography of the chest, abdomen and pelvis (CT) in the investigation of patients (pts) aged > 50 referred to the urgent suspected cancer (USC) pathway for GI malignancies. We evaluated its accuracy in detecting upper GI, lower GI and extraluminal malignancies in a cohort of consecutive pts presenting with and without UA. Methods: We retrospectively analysed characteristics and outcomes of 350 consecutive GI USC referrals (07/2010–07/2012): 200 (Group A) presented with UA and were investigated with OGD (178, 89%), COL (70, 39%) and CT (157, 78%, with 138, 87% aged > 50 years). The diagnostic outcomes were compared with a second group of 150 pts (Group B) referred with alarm symptoms (unintentional weight loss, abdominal pain, progressive dysphagia) who underwent OGD (91, 60%), COL (32, 21%) and CT (139, 93%, with 121, 89% aged > 50 years). Results: Group A had a mean age of 70 years (range 22–96), 51% males, mean haemoglobin (Hb) of 10.2 (5–13.8) g/dL. Pts in Group B had a mean age of 67 years (range 20–92), 60% males, mean Hb 13.9 (11.5–17.5) g/dL. Malignancy was diagnosed in 38 (19%) Group A and 17 (12%) Group B patients (p = 0.07). The proportion of malignant cases diagnosed endoscopically was not different across the studied groups (4/176, 2% and 7/86, 8% for OGD and COL in Group A; 5/91, 6% and 3/32, 9% in Group B, p = 0.3). Conversely, the rate of incident cancers identified by CT favoured Group A (33/157, 21% vs. 10/139, 7%, p < 0.001), where 71% of the incident cancers were extraluminal and diagnosed in pts > 50 (29/33, 87%). Conclusion: Concurrent CT can optimise the detection of malignancy in pts over the age of 50 referred under the GI USC pathway, with subjects presenting with unexplained anaemia achieving the greatest diagnostic benefit. We therefore propose that CT should be incorporated within the routine investigation pathway of anaemia in the over 50s. Disclosure of Interest: None Declared.